Looking at the intractability of the Israeli/Palestine conflict with a focus on the construction of identity - Motala, Nargis (Department of Political Studies, 2017)
Research on intractable conflicts is concerned primarily with investigating the causes and conditions of conflict that contribute to its intractable nature. Often, a key starting point in the examination of intractable conflicts is to explore the relationships between the different processes driving the conflict. Prominent authors investigating the nature of intractable conflicts seek to provide a theoretical understanding of conflict, with the aim of facilitating a deeper understanding of what allows these conflicts to flourish. This dissertation will look specifically at the intractability of the conflict between Israel and Palestine, and evaluate the factors that have contributed to sustaining this conflict. This analysis, which will seek to present an understanding of how the construction of identity in relation to "the Other" has hindered viable options for sustainable peace in the region, draws on John Paul Lederach's work on conflict transformation. Transformation, Lederach argues, provides not only a lens through which to understand certain aspects of conflict but also an overarching framework to make sense of the conflict as a whole (Lederach, 2003). The central and interrelated themes of this dissertation are the competing identities claimed by Israel and Palestine in relation to the on-going conflict. Differing constructions of identity contribute to the intractability of the conflict and is echoed through the respective narratives. After presenting an analysis of the failed attempts at peace and the various negotiation phases that have taken place, the discussion will try to understand why these attempts have been unsuccessful. The main argument presented is that there is need for increased conflict awareness and understanding of the dynamics of the situation. Peace processes need to address the underlying causes and patterns of the conflict by taking into consideration the nature of the conflict, if they are to be effective. Once this is established, attention can then be turned to addressing other issues of concern, such as the status of Jerusalem, border disputes, the right of return, issues over sovereignty and security and so forth. Mechanisms to address these issues should be premised on an understanding that the conflict environment is constantly changing; consequently, approaches to peace need to be evaluated at all stages and, if necessary, adjusted to fit the shifting context.